2020: Estudiantes, emociones, salud mental y pandemia (Investigaciones) - Fernández Poncela, Anna María (2021)
This text’s objective is an approach to university students’ emotions in times of pandemics and confinement. The importance of emotions in education and in general is reviewed, first of all. Second, the importance of emotions in times of change or catastrophe. Both questions from the theory and conceptualization and according to the literature. Thirdly, there is an approach to emotions in 2020, from the gaze and stories of the students of the Universidad Autónoma Metropolitana, Xochimilco unit, in Mexico City, based on a mixed methodological approach, through a survey in the educational center to the student body, and using reports requested from a group of university students. Fear and uncertainty about the situation stand out, on the one hand. On the one hand, sadness, stress, and fatigue stand out, which is related to post-traumatic shock and chronic fatigue, part of people’s mood and mental health in times of crisis.